Spatio-temporal variation of dung beetle (Coleoptera: Scarabaeidae) assemblages in a community ecological reserve of southeastern Mexico - Diana A. Ahuatzin; Wesley Dáttilo; Fernando Escobar-Hernández; Albina Demeza; Lucrecia Arellano (Revista Mexicana de Biodiversidad)
Despite the relevance of community ecological reserves, little is known about changes in spatio-temporal biodiversity patterns in these reserves. Here, we analyzed the spatio-temporal dynamics of the dung beetle assemblages in 4 different environments (primary forest, riparian vegetation, secondary forest, and pasture) in the Bajlum Pakal Community Ecological Reserve, in Chiapas, Mexico. We found that the spatial dynamics showed differences among the analyzed environments, with higher diversity in the tropical rainforest and riparian vegetation. The temporal dynamics did not present a relationship with the richness and diversity of species; therefore, spatial dynamics were more important for explaining the diversity of beetles from all environments. When evaluating the spatial turnover, we found that the most important component of β diversity was β2 (between environments), which suggests that the environmental variation provided by the great spatial heterogeneity of the environments modulates the diversity patterns of beetles in this reserve. Conservation strategies must consider changes in the spatio-temporal dynamics that modulate species assemblages to determine their responses to changes in land use. It is important to maintain the existence of community ecological reserves that conserve biodiversity and connectivity in tropical landscapes, as well as the quality of life of its inhabitants.